Construction et représentation de la mémoire collective dans les entrées triomphales au XVIe siècle - Russell, Nicolas (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2009)
In sixteenth-century France, the triumphal entry was closely tied to the notion of collective memory. This article defines the concept of collective memory as it is articulated in sixteenth-century texts, retraces the history of the relationship between this notion and the triumphal entry, and, in analyzing several texts tied to entry ceremonies, explores how such texts address triumphal entries’ role in the production of collective memory—as opposed to its preservation, which is the typical focus in discussions of the relationship between collective memory and historiographical or poetic works during this period.